2009
DOI: 10.1177/1087057109342126
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of RecA Activity Discovered by High-Throughput Screening: Cell-Permeable Small Molecules Attenuate the SOS Response in Escherichia coli

Abstract: The phenomenon of antibiotic resistance has created a need for the development of novel antibiotic classes with nonclassical cellular targets. Unfortunately, target-based drug discovery against proteins considered essential for in vitro bacterial viability has yielded few new therapeutic classes of antibiotics. Targeting the large proportion of genes considered nonessential that have yet to be explored by high-throughput screening, for example, RecA, can complement these efforts. Recent evidence suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…The search for site-specific recombination inhibitors (focused on transposon Tn3) started a quarter of century ago (49). Possible metal-chelate RecA inhibitors have been proposed as transition metal complexes (based on metal-dependent initia-tion of RecA aggregation), nucleotide analogs, structured peptides, and polysulfated naphthyl compounds (75,76,151). Unfortunately, these molecules are not cell permeable or have a pleiotropic effect on live bacteria.…”
Section: Promiscuity Inhibitors (I) Inhibitors Of Interbacterial Dismentioning
confidence: 99%
See 1 more Smart Citation
“…The search for site-specific recombination inhibitors (focused on transposon Tn3) started a quarter of century ago (49). Possible metal-chelate RecA inhibitors have been proposed as transition metal complexes (based on metal-dependent initia-tion of RecA aggregation), nucleotide analogs, structured peptides, and polysulfated naphthyl compounds (75,76,151). Unfortunately, these molecules are not cell permeable or have a pleiotropic effect on live bacteria.…”
Section: Promiscuity Inhibitors (I) Inhibitors Of Interbacterial Dismentioning
confidence: 99%
“…Unfortunately, these molecules are not cell permeable or have a pleiotropic effect on live bacteria. Recently, a high-throughput target-based screening approach has permitted the identification of a new class of small, permeable compounds that can attenuate the SOS response in living bacteria (117,150,151), Conjugative plasmids have a natural RecA inhibitor, PsiB (108), and research in natural systems of controlling recombination will eventually be of interest. Finally, investigation on HIV-1 has yielded a large number of integrase inhibitors, which eventually could be tested for inhibition of resistance gene acquisition by genetic platforms (58; J. C. Galán, personal communication).…”
Section: Promiscuity Inhibitors (I) Inhibitors Of Interbacterial Dismentioning
confidence: 99%
“…Antibacterial strategies have included use of antimicrobial cationic peptides (AMPs) (7); cell membrane permeabilization (7); molecular chaperones (e.g., heat shock proteins) (4); inhibitors of RecA-mediated strand exchange (34); inhibitors of DNA synthesis (6); inhibitors of penicillinbinding protein production (18); and use of efflux pump inhibitors or inhibitors of beta-lactamase expression (27). Despite almost 20 years of intense research, none of these agents deemed useful in vitro have progressed to clinical use.…”
mentioning
confidence: 99%
“…It was shown that the main generator of resistance mutations is the SOS-or error-prone repair system. [4] In order to compensate for the negative effects identified in the works of Cirz and Wigle et al, [3,5] it was proposed to synthesize new compounds, which would be able to switch off the launch of SOS-response and thus increase the sensitivity of the bacterial population to antibiotics. Currently, several laboratories are conducting screening for SOS-response inhibitors that would prevent the rapid development of bacterial resistance to antibiotics.…”
Section: Introductionmentioning
confidence: 99%